Voluntary Agreements under Endogenous Legislative Threats - Matthieu Glachant (Fondazione Eni Enrico Mattei (FEEM), 2003)
The paper analyzes the welfare properties of voluntary agreements (VA) with polluters, when they are obtained under the legislative threat of an alternative stricter policy option. In the model, the threat is an abatement quota. Both the threat and its probability of implementation are endogenous. The latter is the outcome of a rent-seeking contest between a green and a polluter lobby group influencing the legislature. We show that a welfare-improving VA systematically emerges in equilibrium and that it is more efficient than the pollution quota. We also discuss various VA design aspects.
Keywords: D72; Q28; 330; Environmental policy; voluntary agreements; bargaining; legislatures; rent seeking; rent-seeking contests; Selbstverpflichtung; Umweltpolitik; Verhandlungen; Rent-Seeking; Umweltstandard; Theorie